ANTIMYCOTIC ACTIVITY OF ACTIVATED ZINC PYRITHIONE IN RELATION TO MALASSEZIA IN PATIENTS WITH ATOPIC DERMATITIS - E.V. Golysheva; A.M. Glushakova; A.N. Pampura; M.A. Mokronosova (Педиатрическая фармакология)
The article illustrates the results of a study whose purpose was to determine the antimycotic action of activated zinc pyrithione (AZP) against Malassezia in patients with atopic dermatitis (AD). 30 patients diagnosed with AD and aged 3 to 18 years were studied. A mycological study that aimed to identify Malassezia was done by the scraping method and skin surface collection using a cotton ball on a 1 cm2 area, with further yeast maintenance procedure in a selective environment. The activated zinc pyrithione in the form of cream was applied on children’s skin of the left shoulder and forearm twice a day. Nothing but a moisturizing cream was applied to the skin on the right shoulder and forearm. The samples for mycobiota were taken on both sides three times: before AZP treatment, 1 and 2 weeks after treatment. As a result of treatment, a two-fold reduction in skin colonization with Malassezia just in a week’s time (up to 102–105 КОЕ/cm2). The significant dynamics was observed in the modification of species diversity which got more sparse in skin areas where activated zinc pyrithione cream was applied. The follow-up results confirm that AZP has a moderate antimycotic effect. Key words: atopic dermatitis, treatment, activated zinc pyrithione, antimycotic action, children. (Pediatric Pharmacology. – 2010; 7(6):58-62)